Prospects for Foamy Viral Vector Anti-HIV Gene Therapy - Arun K. Nalla; Grant D. Trobridge (Biomedicines, 2016)
Stem cell gene therapy approaches for Human Immunodeficiency Virus (HIV) infection have been explored in clinical trials and several anti-HIV genes delivered by retroviral vectors were shown to block HIV replication. However, gammaretroviral and lentiviral based retroviral vectors have limitations for delivery of anti-HIV genes into hematopoietic stem cells (HSC). Foamy virus vectors have several advantages including efficient delivery of transgenes into HSC in large animal models, and a potentially safer integration profile. This review focuses on novel anti-HIV transgenes and the potential of foamy virus vectors for HSC gene therapy of HIV.